2021
DOI: 10.1021/acs.jpclett.0c03598
|View full text |Cite
|
Sign up to set email alerts
|

Segmented Ag–Au–Ag Heterojunction Nanorods: Pressure-Assisted Aqueous-Phase Synthesis and Engineered Femtosecond-to-Nanosecond Dynamics

Abstract: Segmented metal−metal heterostructure nanorods/nanowires are very promising for development in photoelectric devices, wearable electronics, biomedicine, and energy storage due to unique surface and interface and adjustable electronic and optical properties. Regretfully, most of the segmented heterojunctions are presently synthesized in organic solvent, and its electronic dynamics is still rarely studied and poorly understood. Here, we reported a pressure-assisted one-step aqueous-phase strategy to successfully… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
2
6
0
Order By: Relevance
“…As shown in Figure 1e, the lattice fringe with interplanar spacings of 0.24 and 0.20 nm can be assigned to the {111} and {200} planes of face-center cubic (fcc) Ag, respectively. 33 The SAED pattern displayed in Figure 1f could be indexed to two sets of diffraction patterns (⟨112⟩ and ⟨001⟩) of Ag, which is consistent with the structure of pentatwinned AgNRs. 34 Based on these results, it is suggested that the AgNRs possessed a pentatwinned structure and the deposition of Ag proceeded along the ⟨110⟩ direction from mainly one side of an Au decahedral seed.…”
Section: ■ Results and Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…As shown in Figure 1e, the lattice fringe with interplanar spacings of 0.24 and 0.20 nm can be assigned to the {111} and {200} planes of face-center cubic (fcc) Ag, respectively. 33 The SAED pattern displayed in Figure 1f could be indexed to two sets of diffraction patterns (⟨112⟩ and ⟨001⟩) of Ag, which is consistent with the structure of pentatwinned AgNRs. 34 Based on these results, it is suggested that the AgNRs possessed a pentatwinned structure and the deposition of Ag proceeded along the ⟨110⟩ direction from mainly one side of an Au decahedral seed.…”
Section: ■ Results and Discussionsupporting
confidence: 64%
“…The high-resolution TEM (HRTEM) image in Figure d also shows the heterostructure of Ag–Au nanorods, evidenced by the different contrast of the two elements on the tip. As shown in Figure e, the lattice fringe with interplanar spacings of 0.24 and 0.20 nm can be assigned to the {111} and {200} planes of face-center cubic (fcc) Ag, respectively . The SAED pattern displayed in Figure f could be indexed to two sets of diffraction patterns (⟨112⟩ and ⟨001⟩) of Ag, which is consistent with the structure of pentatwinned AgNRs .…”
Section: Resultssupporting
confidence: 60%
“…Well-defined and high-yield (>90%) Ag−Au−Ag HJNRs were successfully synthesized via an unprecedented one-step aqueous-phase method according to our developed method. 17 Au nanodecahedrons (i.e., single dark objects in Figures 1a and S1) were first formed, and subsequently Ag atoms were deposited into the (111) crystalline plane of Au nanodecahedrons and grew along the 1D direction (Figure S1). The Ag−Au−Ag HJNRs structure is formed by growing Ag nanorods on the Au nanodecahedron core along each side, which is assigned as the Ag−Au−Ag heterojunction nanorods (HJNRs).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Recently, we have successfully synthesized Ag-Au-Ag HJNRs through using a one-step aqueous-phase method, in which we realized sequential growth of Au and Ag nanocrystals in aqueous (not organic) solution without using a seed or a template. 2 A relatively high temperature, slow reaction speed, and considerable difference between two precursor concentrations were central for the preparation of Ag-Au-Ag HJNRs. A relatively high temperature (ca.…”
Section: ■ Introductionmentioning
confidence: 99%
“…One-dimensional (1D) bimetallic nanostructures, especially 1D segmented metal nanocrystals, have stimulated extensive research enthusiasm because of their synergistic effect and prominent optical and electrical performance , and potential applications in catalysis, , photoelectric devices, , chips, , SERS, , and tumor imaging . To acquire desirable properties and promising applications, it is very important to fabricate well-defined, high-quality, and structure-controlled 1D segmented metal nanocrystals via solution-phase strategies.…”
Section: Introductionmentioning
confidence: 99%